Evaluation effect of Pleurotus ostreatus on some virulence factors in Aspergillus spp - Walaa Yas Lahmood (Al-Qadisiyah Journal of Pure Science, 2022)
This study include isolation of some types of Aspergillus sp from different sources such as ( soil, vegetables), three types appeared; Aspergillus fumegates , Aspergillus nidulans and Aspergillus ochracaeus ,then  tested the virulence factors of these fungi such as production of these enzymes (proteinase ,phospholipase ,heamolycin ,lipase and urease ) , the three types give positive result for production of  phospholipase ,heamolycin  ,lipase and urease; the enzyme proteinase product only from A. ochracaeus .also tested the inhibitory effect of  the Pleurotus ostreatus  filter in concentration 30%  and some antifungal drugs ( Fluconazole , miconazole and nystatin ) in concentration 20%  on the radial growth of these fungi and found that the fungus filter and antifungal drugs have high inhibitory effect on growth